Management of Excursion Activity in the Context of Cultural and Cognitive Tourism as a Type of International Economic Activities: Theoretical Aspects (Economics and region, 2020)
The purpose of the article is to determine the main theoretical aspects of the management of cultural and educational tourism, a visit to historical, cultural or geographical attractions. This type of tourism is one of the most popular and most popular types of tourism today, and also forms a significant share of international trade in the world. In the article, the authors define the main aspects of managing excursion activities and positioning the territory of tourist services. Every year, tourism is developing more and more and reaching a new level. Under the influence of this, the modern tourist becomes more informed about the natural and cultural values of different localities. Therefore, the demand for excursion routes is increasing, and at the same time the requirements for the level of service and quality of services are increasing, too. The current market of tourist services covers a significant range of cultural and entertainment services, and one of the most common types of services both in Ukrainian and foreign tourism is an excursion tour. The main purpose of which is to familiarize with the cultural and historical heritage of a city or country. An integral part of the sightseeing tour is a route that shows the entire journey. The development of the route scheme and its software are inextricably linked parallel processes to which management tools are applied. So the relevance of the topic of the article is due to the fact that at the present stage of development of tourism activities, the number and quality of excursion trips should be increased to meet the needs of tourists, which is impossible without the use of modern methods and models of management.
Keywords: management; international economic activity; tourist services; international services market